Análise sobre desempenho térmico estrutural - GOMES, Gisele Fabiane do Nascimento (2022)
There are several types of materials on planet Earth, this research aims to compare different materials used in housing constructions for thermal performance purposes. The comparisons made take into account traditional and alternative materials. Traditional materials are those of common sense, found in most residential houses, such as ceramic brick, ceramic tile and ceramic floor, etc. Alternative materials are far from common sense, they are materials often made of composites, tiles made of polymers and raw earth brick (Adobe) were used in the research. Each material has thermal characteristics such as thermal conductivity, specific heat, density, among others, due to these characteristics the materials respond differently to a given climate situation, in order to find the material with the best thermal insulation for the climate of the city of Belém-Pa comparative analysis is performed. The comparative analysis between traditional and alternative materials is based on the internal air temperature in ºC, which are influenced by internal and external loads in a standard housing structure, based on this temperature, the thermal insulation of each combination of materials can be analyzed.